Local TNFR1 signaling licenses murine neutrophils for increased TLR-dependent cytokine and eicosanoid production - Deguine, Jacques (J Immunol, 2017)
Neutrophils are generally the first immune cells recruited during the development of sterile or microbial inflammation. As these cells express many innate immune receptors with the potential to directly recognize microbial or endogenous signals, we set out to assess whether their functions are locally influenced by the signals present at the onset of inflammation. Using a mouse model of peritonitis, we demonstrate that neutrophils elicited in the presence of C-type lectin receptor ligands have an increased ability to produce cytokines, chemokines and lipid mediators in response to subsequent Toll-like receptor stimulation. Importantly, we found that licensing of cytokine production was mediated by paracrine TNFα-TNFR1 signaling rather than direct ligand sensing, suggesting a form of quorum sensing among neutrophils. Mechanistically, licensing was largely imparted by changes in the post-transcriptional regulation of inflammatory cytokines, whereas production of IL-10 was regulated at the transcriptional level. Altogether, our data suggest that neutrophils rapidly adapt their functions to the local inflammatory milieu. These phenotypic changes may promote rapid neutrophil recruitment in the presence of pathogens while limiting inflammation in their absence.